2017
DOI: 10.1111/mmi.13612
|View full text |Cite
|
Sign up to set email alerts
|

The GpsB files: the truth is out there

Abstract: Peptidoglycan (PG), an essential stress-bearing component of the bacterial cell wall, is synthesised by penicillin binding proteins (PBPs). PG synthesis at the cell division septum is necessary for constructing new poles of progeny cells, and cells cannot elongate without inserting new PG in the side-wall. The cell division regulator GpsB appears to co-ordinate PG synthesis at the septum during division and at the side-wall during elongation in rod-shaped and ovococcoid Gram-positive bacteria. How the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Their identities are captured in imaginative cartoons suggesting the complexity of the protein-protein interaction network (Egan & Vollmer, 2013; Massidda et al , 2013; Szwedziak & Lowe, 2013; Fleurie et al , 2014; Egan & Vollmer, 2015; Leclercq et al , 2017; Lewis, 2017). A credible measure of the inchoate understanding of LT function is the absence of an LT in all of these cartoons.…”
Section: Resultsmentioning
confidence: 99%
“…Their identities are captured in imaginative cartoons suggesting the complexity of the protein-protein interaction network (Egan & Vollmer, 2013; Massidda et al , 2013; Szwedziak & Lowe, 2013; Fleurie et al , 2014; Egan & Vollmer, 2015; Leclercq et al , 2017; Lewis, 2017). A credible measure of the inchoate understanding of LT function is the absence of an LT in all of these cartoons.…”
Section: Resultsmentioning
confidence: 99%
“…A screen for gpsB suppressors in S. pneumoniae did not yield reoM mutations (and these strains do not contain reoY , consistent with a subordinate function for this gene), but instead suppressor mutations were found that affect phpP , which encodes a Ser/Thr protein phosphatase that acts in concert with StkP, the PASTA-eSTK of this organism (57, 58). Absence or inactivation of PhpP triggered an increase in StkP-dependent protein phosphorylation levels in the pneumococcus (57, 59).…”
Section: Discussionmentioning
confidence: 98%